Approaches and Features of Biologically Intensive Farming system - Rajbhandari , Binayak Prasad (Nepalese Journal of Agricultural Sciences, 2025)
In order to substantially reduce the negative impact of conventional petro chemical farming and to address the issues of poverty, agri-production, environment conservation and food security, it is high time to adopt biologically intensive farming (BIF) system around the globe. It plays pivotal role in conserving natural resources and improves soil health and agri-production. This article addresses the importance, approaches and features of biologically intensive farming system.